2020
DOI: 10.1002/cae.22342
|View full text |Cite
|
Sign up to set email alerts
|

A framework utilizing augmented reality to improve critical thinking ability and learning gain of the students in Physics

Abstract: Physics is a branch of science that deals with different properties of energy and matter. Most of the principles of Physics are based on Mathematics, Mechanics, Optics, Electricity, Magnetism, and Thermodynamics. It is often difficult for students to grasp concepts as they cannot visualize the phenomena, resulting in compounding the problem of lack of interest in STEM subjects. Augmented reality (AR) can be effective in providing better visualization and interaction with real‐like three‐dimensional virtual obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 35 publications
2
29
0
3
Order By: Relevance
“…Faridi et al believe that virtual reality can effectively provide better visualization effect, and interaction with real 3D virtual reality can simplify the object of learning experience. An experimental study was carried out to determine that virtual reality intervention has a significant positive impact on students' learning and critical thinking [ 55 ]. Virtual reality technology can promote the interaction between learners, environment, and learning content.…”
Section: Model Framework Of Virtual Reality Technology Promoting the Development Of Clinical Thinking Of Medical Studentsmentioning
confidence: 99%
“…Faridi et al believe that virtual reality can effectively provide better visualization effect, and interaction with real 3D virtual reality can simplify the object of learning experience. An experimental study was carried out to determine that virtual reality intervention has a significant positive impact on students' learning and critical thinking [ 55 ]. Virtual reality technology can promote the interaction between learners, environment, and learning content.…”
Section: Model Framework Of Virtual Reality Technology Promoting the Development Of Clinical Thinking Of Medical Studentsmentioning
confidence: 99%
“…On the other hand, from the results of the research that has been shown in the previous section, it also explicitly explains that AR can be used effectively and efficiently as a learning media to improve students' HOTS. The development of augmented reality-based learning media is very possible to do in order to improve students' critical thinking skills (Faridi, 2021). The use of GS as a media to improve students' DLS also needs to be tried by teachers in the learning process.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the research that has been shown in the previous section, also explicitly explain that AR can be used effectively and efficiently as a learning medium to improve students' HOTS. The development of augmented reality-based learning media is very possible to do to improve student's critical thinking skills (Faridi, Tuli, Mantri, Singh, & Gargrish, 2021). The use of GS as a medium to improve students' DLS also needs to be tried by teachers in the learning process.…”
Section: Resultsmentioning
confidence: 99%